PORTABLE INFORMATION DISPLAY DEVICE - MATSUMURA HIDETOSHI (2009)
PROBLEM TO BE SOLVED: To provide a portable information display device with improved operability in displaying a plurality of image information by using a display device which can simultaneously display the plurality of different image information on the display screen wherein the image information are different between in viewing the display screen from a right side, and in viewing the display screen from a left side. SOLUTION: The portable information display device comprises the display screen 21 for displaying the image information, a multi-view display part 10 which can simultaneously display the two image information, which is different between in viewing the display screen 21 from the right side and in viewing the display screen 21 from the left side, on the display screen 21, first and second image generation parts 54a, 54b for generating two image information respectively based on operation of an operation key by a user, an inclination detection part 51 for detecting inclination of the display screen 21 with respect to the user, and an operation subject selection part 53 for outputting an input signal based on the operation of the operation key to either of the first and second image generation parts 54a, 54b based on a detection result by the inclination detection part 51. COPYRIGHT: (C)2009,JPO&INPIT